Reversible changes in serum immunoglobulin galactosylation during the immune response and treatment of inflammatory autoimmune arthritis. Issue 8 (4th September 2008) - Van Beneden, K; Coppieters, K; Laroy, W; De Keyser, F; Hoffman, I E; Van den Bosch, F; Vander Cruyssen, B; Drennan, M; Jacques, P; Rottiers, P; Verbruggen, G; Contreras, R; et al.
Abstract : Objectives: Improved DNA sequencer-aided fluorophore-assisted carbohydrate electrophoresis (DSA-FACE) technology was used to monitor the changes in the galactosylation status of serum immunoglobulins during the immune response and therapy of autoimmune arthritis. Methods: Collagen-induced arthritis (CIA) was induced in susceptible DBA/1 mice and the undergalactosylation status (UGS) of serum immunoglobulins was determined using the improved DSA-FACE technology. Prophylactic intravenous tolerisation with type II collagen as well as semitherapeutic treatment with dexamethasone (DEX) were performed and UGS was analysed. Next, the serum immunoglobulin glycosylation profiles of patients with rheumatoid arthritis (RA) and spondyloarthropathy (SpA) were studied and changes in the UGS scores during anti-tumour necrosis factor (TNF)α therapy followed. Results: In the longitudinal CIA study, the undergalactosylation state of immunoglobulins was found to be significantly correlated with the clinical arthritis scores. Upon collagen-specific tolerisation as well as glucocorticoid semitherapeutic treatment, improvement of the clinical arthritis scores correlated with decreased levels of UGS. It was also demonstrated that withdrawal of DEX was associated with an increased UGS score. Interestingly, reversibility in the UGS was also shown during treatment of patients with RA and SpA with anti-TNFα. Conclusions: These findings demonstrate that the UGS of serum immunoglobulins changes during the disease course of CIA and that this UGS is inhibited by antigen-specific and antigen-independent treatment procedures. The observation that Ig galactosylation is a reversible process is also documented during treatment of patients with RA and SpA with anti-TNFα.